MITOCHONDRIOCENTRIC PATHWAY TO CARDIOMYOCYTE NECROSIS IN ALDOSTERONISM: CARDIOPROTECTIVE RESPONSES TO CARVEDILOL AND NEBIVOLOL - Cheema, Yaser (2011)
Foci of fibrosis, footprints of cardiomyocyte necrosis, are scattered throughout the failing myocardium and are a major component to its pathologic remodeling. Understanding pathogenic mechanisms contributing to hormone-mediated necrosis are therefore fundamental to developing cardioprotective strategies. In this context, a mitochondriocentric signal-transducer-effector (MSTE) pathway to necrosis is emerging. Our first objective, using cardiomyocytes and subsarcolemmal mitochondria (SSM) harvested from rats receiving 4 wks aldosterone/salt treatment (ALDOST), was to identify major components of this pathway. Secondly, to validate this pathway we used mitochondria-targeted pharmaceutical interventions as cardioprotective strategies using 4 wks cotreatment with either carvedilol (Carv) or nebivolol (Nebiv). Compared to controls, we found 4 wks ALDOST to be accompanied by: elevated cardiomyocyte free [Ca(2+)](i) and SSM free [Ca(2+)](m); increased H(2)O(2) production and 8-isoprostane in SSM, cardiac tissue and plasma; and enhanced opening of mitochondrial permeability transition pore (mPTP) and myocardial scarring. Increments in antioxidant capacity augmented by increased cytosolic free [Zn(2+)](i) were overwhelmed. Cotreatment with either Carv or Nebiv attenuated [Ca(2+)](i) and [Ca(2+)](m) overloading, prevented oxidative stress and reduced mPTP opening while augmenting [Zn(2+)](i) and conferring cardioprotection. Thus, major components of the MSTE pathway to cardiomyocyte necrosis seen with ALDOST include intracellular Ca(2+) overloading coupled to oxidative stress and mPTP opening. This subcellular pathway can be favorably regulated by Carv or Nebiv cotreatment to salvage cardiomyocytes and prevent fibrosis.